ELECTRONIC CUSTOMER RELATIONSHIP MANAGEMENT (E-CRM) BERBASIS DESKTOP DAN WEBSITE PADA PT.ZIMA TRANSLOGISTIC - Rachmat Hidayat (Jurnal Techno Nusa Mandiri, 2013)
The rapid development of information technology is happening now in our country especiallyIndonesia, Technology no longer a strange, even needed to support the performance of an organization. For now, without the support of a company's information technology may be impossible to develop. In this context, the information can be said to be the key to support and improve the management of the company in order to win the competition that the longer the more increase. One method that can be used to improvise and improve services and promotions to customers is with CRM is Customer Relationship Management, PT. Zima Translogistic company engaged in the expedition with many customers in desperate need of the system very quickly and precisely so that the customer will get the satisfaction of administrative services and information accurate, these problems made the system desktop-based e-CRM for customer transactions and website to get the information related to customer transactions.